Health Related Quality of Life and Associated Factors among Burn Patients at Two Burn Specialty Hospitals of Kathmandu - Gorkhali, Binu; Nakarmi, Kiran; Amatya, Mrigendra (Nepal Medical College Journal, 2025)
Burn injury has high incidence in Nepal and the outcome is generally poor. Besides physical health, burn also impacts many other aspects of life, including quality of life. This study aimed to study health-related life quality among burn patients in Nepal and explore associated sociodemographic and burn-related factors. A descriptive study was conducted in two burn specialty hospitals of Kathmandu. Burn patients 18 years or older, after acute burn management, and admitted or attending the hospitals' out-patient clinic were studied. Data were collected through face-to-face interview and patients’ hospital records, using the Burn Specific Health Scale Brief - Nepali version, consisting 40 items under three main domains (physical, burn-specific, and social-emotinal). Among 337 burn patients, 154 were males (45.7%) and 183 females (54.3%); mean age was 39.7 years (±16.9). The median score was 115 (IQR 97-146) and overall, 72.4% patients had poor health related quality of life. Poor health-related quality of life was found in 92.3% for physical function domain, 86.6% for burn specific domain and 70.3% for social-emotional function domain. Active age group, nuclear family type, higher education, deeper burn injury, larger affected skin area, presence of complication were significantly associated with poor health-related quality of life.